Trends in Binge and Heavy Drinking, Alcohol-Related Problems, and Combat Exposure in the U.S. Military. (24th August 2013) - Bray, Robert M.; Brown, Janice M.; Williams, Jason
Abstract : Population-based Department of Defense health behavior surveys were examined for binge and heavy drinking among U.S. active duty personnel. From 1998–2008, personnel showed significant increases in heavy drinking (15% to 20%) and binge drinking (35% to 47%). The rate of alcohol-related serious consequences was 4% for nonbinge drinkers, 9% for binge drinkers, and 19% for heavy drinkers. Personnel with high combat exposure had significantly higher rates of heavy (26.8%) and binge (54.8%) drinking than their counterparts (17% and 45%, respectively). Heavy and binge drinking put service members at high risk for problems that diminish force readiness and psychological fitness.